LncRNA TUG1 Promotes Apoptosis, Invasion, and Angiogenesis of Retinal Endothelial Cells in Retinopathy of Prematurity via MiR-145-5p - Wang, Yuexia; Wang, Yue; Wang, Xue; Ma, Yuan; Li, Zhaojin; Di, Yu (Frontiers in Medicine, 2022)
Abstract: Purpose: Retinopathy of prematurity (ROP) is a common retinal vascular disease in premature neonates. In recent years, there is increasing evidence that the long non-coding RNA taurine upregulated gene 1 (TUG1) plays a regulatory role in vas-cular diseases, suggesting a potential role for TUG1 in vascular endothelial cells. We hypothesized that TUG1 may be associated with ROP. Our aim, therefore, was to ex-plore the biological functions of TUG1 in aberrant retinal development. Methods: We used the mouse oxygen-induced retinopathy (OIR) model to simulate the pathological changes of retinal in ROP. Quantitative real-time polymerase chain reaction was used to detect the expression of TUG1, miR-145-5p and cellular com-munication network factor 1 (CCN1). Human retinal endothelial cells (HRECs) were treated with CoCl2 to mimic hypoxia conditions. Cellular functional changes were observed after transfection with RNAi-TUG1 and miR-145-5p mimics. The apoptosis of HRECs was detected by flow cytometry, the migration ability was detected by wound healing and transwell migration assays, and the ability of angiogenesis was detected by tube formation assay. The potential binding sites between TUG1, miR-145-5p, and CCN1 were verified by dual-luciferase reporter assays. The degree of retinopathy was evaluated by staining retinal sections with hematoxylin and eosin, and the expression of CCN1, HIF-1α, VEGF, caspase-3, Bcl-2, IL-1 β, and TNF- α protein was analyzed by western blotting and immunohistochemistry. Results: In the retina tissue of OIR mice, TUG1, miR-145-5p, and CCN1 were dif-ferentially expressed. Knocking down TUG1 attenuated apoptosis, migration, and angiogenesis induced by hypoxia on HRECs, as did miR-145-5p overexpression. Results from reporter assays indicate direct interactions between TUG1, miR-145-5p, and CCN1. Intravitreal injection of miR-145-5p mimics reduced the degree of reti-nopathy. Conclusions: TUG1 acts as a molecular sponge of miR-145-5p to regulate CCN1 ex-pression and thus regulate the development of retinal neovascularization. This regu-latory mechanism may provide a new theoretical basis for the prevention and treat-ment of ROP.